Chimeric Antigen Receptor T-Cell Therapy: What the Neuroradiologist Needs to Know - Valand, H.A. (AJNR Am J Neuroradiol, 2019)
Chimeric antigen receptor T-cell therapy is an exciting and rapidly emerging “fifth pillar” treatment for hematologic cancers. Unique treatment-related toxicities and cost remain a major hindrance to its widespread application. The commonly faced challenges with this innovative therapy, its neurotoxicity, and manifestation on neuroimaging studies, are reviewed.